Relationship of Job Satisfaction and Demographic Variables in Terengganu Public Universities - Amalyna Radzali, Nur; Abu Bakar, Norsuhaily (International Journal of Engineering and Technology, 2018)
The study on job satisfaction among academic staff at Public Universities in Terengganu is aimed at identifying the level and factors towards their job satisfaction while serving at public universities. This study involved 298 respondents voluntarily. The characteristics of the collected respondents' demographic variables are divided into 9 sections consisting of gender, age, level of education, position of status, service period, position, and other positions within the department. The involved respondents are based on the different levels of academic staff ranging from Assistant Lecturer, Lecturer, Senior Lecturer, Associate Professor, and Professor. Among these respondents were those holding various administrative posts such as Central Director, Dean, Deputy Dean and Head of Department or Head of School. All of the demographic information of these respondents are collected through a survey distributed to them. The results of this finding have been analysed in the form of tables based on the number and percentage of respondents.Â